Medical error analysis in dermatology according to the reports of the North Rhine Medical Association from 2004 to 2018. (4th December 2022) - Lehmann, Lion; Appelbaum, Sebastian; Ostermann, Thomas; Weber, Beate; Hofmann, Silke C.
Summary: Background: Assessment of complaints addressed to the Expert Committee for Medical Malpractice Claims of the North Rhine Medical Association helps to identify quality assurance problems in dermatology. Methods: 333 dermatological reports (years 2004–2018) were allocated to three five‐year intervals in order to show changes of total number of reports and with regard to indications, types of care, defined diagnosis categories, and therapeutic interventions. Statistical analysis was mainly descriptive (SPSS 27). Representative cases are explained in more detail. Results: The number of dermatological reports fell from 119 in the first to 92 reports in the last five‐year interval, along with a decline in treatment error rates (43 % and 29 %) despite an increasing number of procedures across disciplines. 104 reports dealt with (supposed) diagnostic errors, 156 with physical or pharmacological therapies, and 73 reports with surgery. The latter had a low treatment error rate (29 %). Conclusions: In comparison to the number of dermatological treatments in Germany, patient allegations are raised only rarely indicating greater patient satisfaction and/or a lower risk potential in dermatology. Incorrect dosages or device settings, diagnostic errors, and deficits in obtaining informed consent are relevant sources of error as underlined by the presented case reports.